Identification of genetic elements required for Listeria monocytogenes growth under limited nutrient conditions and virulence by a screening of transposon insertion library - Narayanan, Lakshmi; Ozdemir, Ozan; Alugubelly, Navatha; Ramachandran, Reshma; Banes, Michelle; Lawrence, Mark; Abdelhamed, Hossam (Frontiers in Microbiology, 2022)
Listeria monocytogenes, the causative agent of listeriosis, is capable of living in diverse environments ranging from saprophytic to pathogenic as a facultative intracellular parasite. In the current study, a random transposon (Tn) insertion library was constructed in L. monocytogenes strain F2365 and screened to identify genes and pathways affecting in vitro growth and fitness in minimal medium (MM) containing varying single carbohydrate as the sole carbon source. About 2,000 Tn-mutants were screened for impaired growth in MM with one of the following carbon sources: glucose, fructose, mannose, mannitol, sucrose, glycerol, and glucose 6-phosphate. Impaired or abolished growth of L. monocytogenes was observed for twenty-one Tn-mutants with disruptions in genes encoding purine biosynthesis enzymes (purL, purC, purA, and purM), pyrimidine biosynthesis proteins (pyrE and pyrC), ATP synthase protein (atpI and atpD2), branched-chain fatty acids (BCFA) synthesis enzyme (bkdA1), a putative lipoprotein (LMOF2365_2387), and three hypothetical proteins. All Tn-mutants, except the atpD2 mutant, grew as efficiently as wildtype strain in a nutrient rich media. The virulence of twenty-one Tn-mutants was assessed in mice by determining the bacterial concentrations in liver and spleen tissues at 72 hours following intravenous (IV) infection. The most attenuated mutants had Tn insertions in purA, HP64, bkdA1, dUTPase, LP2387, and atpD2, confirming the important role of these genes in pathogenesis. Six Tn-mutants were then tested for ability to replicate intracellularly in murine macrophage J774.1 cells. Significant intracellular growth defects were observed in two Tn-mutants with insertions in purA and HP64 genes, suggesting that an intact purine biosynthesis pathway is important for intracellular growth of L. monocytogens. In conclusion, Tn-mutagenesis identified that biosynthesis of purines, pyrimidine, ATP synthase protein, and BCFA are important for L. monocytogens pathogenesis. Purine and pyrimidine auxotrophs are attenuated in other bacterial pathogens, but our study also revealed novel proteins essential for both growth in MM and listerial virulence.